PERBANDINGAN ANTARA INDEKS MASSA TUBUH KATEGORI NORMAL, OVERWEIGHT, DAN OBESITAS DENGAN RISIKO MENGALAMI PLANTAR FASCIITIS PADA WANITA USIA DEWASA DI KECAMATAN GIANYAR - I Putu Adi Merta; I Made Niko Winaya; I Wayan Sugiritama (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2018)
Elevated body mass can increases plantar pressure, so that causing overstretch the plantar fascia and occurs inflammation. The aims of this study was to compare the risk of having plantar fasciitis in women with normal, overweight, and obese body mass index at Gianyar district. This study is a cross-sectional analytic study. Samples are selected using purposive sampling technique. The samples consists of 3 groups, which amounted to 25 people in each group. Group A was women with normal BMI, group B was women with overweight BMI, and group C was women with obese BMI. The result of pearson chi-square p = 0.022 (p ? 0.05) indicating that there is a significant data distribution difference. The relative risk for overweight-obese compared to normal BMI was RR=3.34 [95% CI 1.09 - 10.16]. Concluded that there is a difference proportion of risk having plantar fasciitis between normal BMI (4%), overweight BMI (10,7%), obesity BMI (16%) and overweight-obese BMI have 3,34 times greater risk of having plantar fasciitis than the normal BMI category. Keywords: Body Mass Index, overweight, obese, plantar fasciitis, women